THE ROLE OF PANGLIMA LAOT TOWARDS FISHERMAN COMMUNITIES IN BANGKA JAYA GAMPONG, DEWANTARA DISTRICT, NORTH ACEH DISTRICT - Setia Budi; Adhiana Adhiana; Muhammad Febriansyah; Dika Saputra (Jurnal Mahasiswa Agribisnis, 2023)
Panglima Laot is the head of the Adat Laot Institute who lives in the midst of a fishing community in Aceh Province with the duty and authority to regulate the fishing system and has the authority to resolve disputes, disputes and violations that occur among fishermen and impose sanctions on the violators in accordance with the provisions of customary law of the sea . This study aims to find out how the role of Panglima Laot is towards fishing communities in Gampong Bangka Jaya, Dewantara District, North Aceh Regency. Data analysis using a Likert scale. The results of the study show that the role of Panglima Laot in fishing communities is very important. The index value based on the distribution of aid is 91.83%, which means it plays a very important role. The index value based on the supervision of Adat Laot is 80, 61% which means a role. The index value based on dispute resolution is 93.11%, which means it plays a very important role. The index value based on Adat Laot law is 60.90%, which means it plays a less role